Ten years of the Interuniversity Institute of Myology - Giorgio Fanò Illic (PAGEPress Publications, 2013)
The Interuniversity Institute of Myology (IIM) has been formally approved in late autumn 2003 by the University of Chieti Board of the first Director, Giorgio Fanò. Many Italian Myologists, coming from Italian Universities such as Università degli Studi di Chieti, Università degli Studi di Brescia, Università degli Studi di Firenze, Università degli Studi di Messina, Università degli Studi di Milano, Università degli Studi di Padova, Università degli Studi di Pavia, Università degli Studi di Perugia, Università degli Studi di Roma 'La Sapienza', Università degli Studi di Siena, who excel in Myology Research, recognized IIM and its potentiality for international joined collaboration.